Contesting sustainable transportation: bicycle mobility in Boston and beyond - Vith, Thomas Arthur; Mössner, Samuel (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
This article traces the social and political aspects of cycling mobility in the Boston area. For some, attracting a certain desirable demographic by investing in bicycle infrastructure is problematic because it could lead to gentrification. Not investing in low-income neighborhoods, however, could be seen as a perpetuation of an unjust distribution of resources. While the bicycle is a common cost-efficient choice among low-income residents, it also symbolizes a privilege for new urban elites, although for very different reasons. Drawing on interview data gathered between 2015 and 2016 with city officials, cycling associations, and transportation planners, the article details the different narratives that unfold in the construction of bicycling infrastructure: First, bicycling has often been conceptualized in the rhetoric of Boston city officials in terms of economic growth. The promotion of cycling helps satisfy the city’s ostensible need to attract or retain a well-educated, young and mobile workforce for whom good bike infrastructure is a criterion when choosing places to work and live. Second, some have observed that bicycle infrastructure in the US is often included in neighborhoods that are undergoing processes of gentrification or have recently been gentrified. Third, bicycle infrastructure improvements have been met with suspicion or resistance by residents in neighborhoods where displacement – or the fear of it – is an issue. This article shows that bicycle mobility in the US is charged with social dynamics which influence the way bicycle mobility is conceptualized, both as a social practice and as a political strategy.